Effect of Decorticated Fermented Prosopis Seed Meal (Prosopis africana) on Growth Performance of Broiler Chicken - Yusuf, N.D.; Ogah, D.M.; Hassan, D.I.; Musa, M.M.; Doma, U.D. (International Journal of Poultry Science, 2008)
Two hundred and forty 7 days old Anak 2000 broiler chicks were used to determine the growth rate and economic of broiler fed decorticated fermented Prosopis africana seed meal (DFPSM). Five experimental diets containing 0, 25, 50, 75 and 100% DFPSM replacement levels for full fat soybean meal were fed to broiler for 8 weeks. The experiments were in a completely randomized design (CRD) with five treatments, each replicated four times with 48 birds per treatment and 12 birds per replicate. The average live weight of broiler ranged from 2500-2850g in each dietary group and were significantly (P < 0.05) affected by dietary treatment, similarly the growth rate and feed conversion ratio were also significantly affected by the dietary treatment (P < 0.05) .The study indicate that 20% inclusion of DFPSM with soybean meal could be used in a broiler diet.